Emotional regulation mechanisms regarding posttraumatic and depressive symptoms in maltreated youth - Ellis, Kinsey; Kearney, Christopher A. (Frontiers in Public Health, 2025)
Maltreated youth are a particularly vulnerable group that often contends with multifaceted mental health challenges, especially symptoms of posttraumatic stress and depression. Emotional dysregulation may have a central role in linking victimization to youth psychopathology in this population, but few have examined the effect of specific mechanisms such as expressive suppression and cognitive reappraisal in this regard. The present study examined these mechanisms vis-à-vis posttraumatic and depressive symptoms in a highly diverse sample of 133 youth aged 11–17 years who were removed from home following maltreatment. Expected positive relationships were found with respect to expressive suppression and total and cluster (i.e., intrusion, avoidance, alterations in cognition and mood, and alterations in arousal and reactivity) posttraumatic stress symptoms as well as depressive symptoms. Conversely, unexpected positive relationships were found with respect to cognitive reappraisal and these symptoms only for specific groups, notably males, younger youth, and those who had not experienced sexual maltreatment. The findings may have implications for tailoring clinical protocols for this vulnerable population, and may offer directions for integrating expressive suppression and cognitive reappraisal into transdiagnostic models of psychopathology in youth.